2005
DOI: 10.1007/s11104-004-1651-z
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic properties of layered soils influence survival of Rhodes grass (Chloris gayana Kunth.) during water stress

Abstract: Survival of vegetation on soil-capped mining wastes is often impaired during dry seasons due to the limited amount of water stored in the shallow soil capping. Growth and survival of Rhodes grass (Chloris gayana) during soil drying on various layered capping sequences constructed of combinations of topsoil, subsoil, seawater-neutralised residue sand and low grade bauxite was determined in a glasshouse. The aim was to describe the survival of Rhodes grass in terms of plant and soil water relationships. The soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 17 publications
2
20
1
Order By: Relevance
“…As observed in earlier studies (e.g. Wehr et al, 2005), soil moisture characteristic curves showed that residue sand had low water retention capacity. The van Genuchten pore size distribution index (n) was 3.58, while α, which is inversely related to the air-entry value was 0.15 kPa − 1 .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…As observed in earlier studies (e.g. Wehr et al, 2005), soil moisture characteristic curves showed that residue sand had low water retention capacity. The van Genuchten pore size distribution index (n) was 3.58, while α, which is inversely related to the air-entry value was 0.15 kPa − 1 .…”
Section: Discussionsupporting
confidence: 81%
“…Botros et al, 2009;Gόmez et al, 2005;Sobieraj et al, 2002), there has been no systematic field evaluation of K s and its spatial variability for artificially constructed ecosystems such as engineered covers. The few studies conducted on mine waste disposal facilities or artificial catchments are based on indirect methods involving analysis of qualitative data on soil structure (Breshears et al, 2005;Buczko et al, 2001), while results of spatial analysis are often not reported probably due to small sample sizes that restrict such analysis (Gerwin et al, 2009;Holländer et al, 2009;Mazur et al, 2011;Wehr et al, 2005). Notable exceptions are two studies conducted in Germany, where geostatistical analysis of hydraulic parameters derived from pedotransfer functions developed for natural soils showed that particle segregation during transportation and dumping, and amelioration practices contributed to spatial variability on lignite mine spoils (Buczko et al, 2001;Buczko and Gerke, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The conventional remediation technique was capping in which a cap of soil from 20-200 cm deep was placed over the RDA (Wehr et al, 2005. A shallow cap can support grasses and herbs whilst deeper caps may support trees and shrubs (Mendez and Maier, 2008).…”
Section: Revegetationmentioning
confidence: 99%
“…0.002 cm min -1 ) (Bell and Meecham, 1978). Residue sand (which is much coarser textured) has a lower water holding capacity than mud but a higher hydraulic conductivity (Wehr et al, 2005.Because of the low macroporosity and hydraulic conductivity of mud, water tends to pond on the surface and the upper layers can become saturated during wet periods of the year. Such waterlogging 17 can limit plant establishment (Pinnock and Gordon, 1992; Zhang et al, 2001; Newson et al, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation